Positive pole piece and preparation method thereof, battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380045035.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-02-14
AI Technical Summary
During the charging and discharging process of the existing lithium-ion battery cathode plate, the conductivity difference between lithium iron phosphate and lithium nickel cobalt aluminate causes excessive release of lithium ions, affecting the cycle performance of the battery cells.
Using a positive electrode plate including a first active material with an olivine structure and a spinel structure and a second active material with a layered structure, the difference in resistivity is controlled to 20≤R2 by arranging the first film layer and the second film layer /R1≤500, which reduces the accumulation of electrons on the surface of the second active material and reduces the risk of excessive lithium ion extraction.
It improves the cycle performance and energy density of battery cells, reduces the risk of fire and explosion, and enhances the reliability and conductive properties of the battery.
Smart Images

Figure CN119452484A_ABST
Abstract
Description
Positive electrode sheet and preparation method thereof, battery cell, battery and electrical device Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device. Background Art
[0002] In recent years, the application scope of lithium-ion batteries has become increasingly wide. They are widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] As a component of a battery cell, the performance of the positive electrode sheet is crucial to the performance of the battery cell. Therefore, how to provide a positive electrode sheet to improve the performance of the battery cell is a technical problem that needs to be solved urgently.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode sheet to improve the performance of a battery cell.
[0006] In order to achieve the above-mentioned objectives, the present application provides a positive electrode plate and a preparation method thereof, a battery cell, a battery and an electrical device.
[0007] In a first aspect, a positive electrode plate is provided, comprising: a positive electrode current collector and a first film layer and a second film layer arranged on the same side of at least one side surface of the positive electrode current collector; wherein the first film layer comprises a first active material, and the first active material comprises at least one of an olivine structure material and a spinel structure material; the second film layer comprises a second active material, and the second active material comprises a layered structure material; the resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 20≤R2 / R1≤500.
[0008] Embodiments of the present application provide a positive electrode sheet comprising a positive electrode current collector and a first film layer and a second film layer disposed on the same side of at least one surface of the positive electrode current collector. The first film layer comprises a first active material comprising an olivine-structured material and a spinel-structured material; the second film layer comprises a second active material comprising a layered material. Battery cells fabricated with the first active material have high reliability, while battery cells fabricated with the second active material have high energy density. The provision of the first and second film layers not only helps balance energy density and reliability of the battery cells, but also reduces the likelihood of the first active material adhering to the surface of the second active material, thereby reducing electrons accumulated on the surface of the second active material and reducing the risk of excessive lithium ion release from the second active material, thereby improving the cycling performance of the battery cells. The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy the following relationship: 20 ≤ R2 / R1 ≤ 500. This minimizes the resistivity difference between the first and second active materials, reducing the effect of electron accumulation on the surface of the second active material on lithium ion release from the second active material, thereby improving the cycling performance of the battery cells. Therefore, the technical solution of the embodiment of the present application is conducive to improving the performance of the battery cell.
[0009] In a possible implementation, the resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 50≤R2 / R1≤300.
[0010] In the above technical solution, 50≤R2 / R1≤300, which is beneficial to further reduce the electrons gathered on the surface of the second active material, thereby further improving the cycle performance of the battery cell.
[0011] In one possible implementation, the resistivity R1 of the first active material is 10 Ω·cm to 80 Ω·cm; alternatively, 20 Ω·cm to 60 Ω·cm. This facilitates the preparation of the first active material while also balancing the conductivity of the first film layer and the cycling performance of the battery cell.
[0012] In one possible implementation, the resistivity R2 of the second active material is 1500Ω·cm to 15000Ω·cm; alternatively, 3000Ω·cm to 9000Ω·cm. This facilitates the preparation of the second active material while also balancing the conductivity of the second film layer and the cycling performance of the battery cell.
[0013] In a possible implementation, the second film layer is located on a surface of the first film layer away from the positive electrode current collector.
[0014] In the above technical solution, the second film layer is located on the surface of the first film layer away from the positive electrode current collector, which is beneficial to reducing the transmission path of lithium ions to the second active material, and is beneficial to exerting the performance of the second active material, thereby improving the energy density and cycle performance of the battery cell.
[0015] In a possible implementation, the first film layer is located on a surface of the second film layer away from the positive electrode current collector.
[0016] In the above technical solution, the first film layer is located on the surface of the second film layer away from the positive electrode current collector. The first film layer is located on the outermost side of the positive electrode current collector. This is beneficial to improving the reliability of the battery cell and reducing the risk of fire and explosion.
[0017] In one possible implementation, the first active material includes a first active material core and a first coating layer coating the first active material core, the first active material core includes at least one of an olivine structure material and a spinel structure material, and the first coating layer includes a carbon material.
[0018] In the above technical solution, coating the first active material core with the first coating layer is beneficial to improving the conductive performance of the first active material.
[0019] In a possible implementation, the olivine structured material includes LiFe 1-x-y Mn x M 1 y PO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M 1 Including at least one of other transition metal elements or non-transition metal elements except Fe and Mn; Optionally, M 1 Including at least one of Cr, Mg, Ti, Al, Zn, W, Nb, Zr; Optionally, the LiFe 1-x-y Mn x M 1 y PO4 includes LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 In this way, the stability of the material with olivine structure is higher, which is beneficial to improve the reliability of the battery cell.
[0020] In a possible implementation, the spinel structure material includes LiMn2O4, LiNi e Mn 2-e At least one of O4, wherein 0<e<2. The battery cell prepared by the spinel structure material has high reliability, which is beneficial to reducing the probability of fire and explosion of the battery cell.
[0021] In a possible implementation, the layered structure material includes LiCoO2, LiMnO2, LiNiO2, LiNi a Co b Mn 1-a-b O2、LiNi c Co d Al 1-c-d O2、nLi2MnO3·(1-n)LiM 2 At least one of O2, where 0<n<1, M 2 The material comprises at least one of Co, Ni, and Mn, and 0<a<1, 0<b<1, 0<a+b<1, 0<c<1, 0<d<1, and 0<c+d<1. The layered structure material has a high specific capacity, which is beneficial to improving the energy density of the battery cell.
[0022] In a possible implementation, the thickness d1 of the first film layer is 40 μm to 160 μm; optionally, 60 μm to 140 μm.
[0023] In the above technical solution, by reasonably setting the thickness of the first film layer, it is beneficial to take into account both the energy density and reliability of the battery cell.
[0024] In a possible implementation, the thickness d2 of the second film layer is 40 μm to 160 μm; optionally, 60 μm to 140 μm.
[0025] In the above technical solution, by reasonably setting the thickness of the second film layer, it is beneficial to take into account both the energy density and reliability of the battery cell.
[0026] In one possible implementation, based on the total weight of the first film layer, the weight percentage of the first active material is 90wt% to 99wt%; optionally, 96wt% to 98wt%; and / or, based on the total weight of the second film layer, the weight percentage of the second active material is 90wt% to 99wt%; optionally, 96wt% to 98wt%.
[0027] In the above technical solution, by reasonably setting the mass ratio of the first active material to the first film layer, it is beneficial to improve the comprehensive performance of the first film layer, and it is beneficial to balance the energy density and reliability of the battery cell and the conductivity and adhesion of the first film layer; by reasonably setting the mass ratio of the second active material to the second film layer, it is beneficial to improve the comprehensive performance of the second film layer, and it is beneficial to balance the energy density and reliability of the battery cell and the conductivity and adhesion of the second film layer.
[0028] In one possible implementation, based on the total weight of the first film layer, the weight percentage of the conductive agent in the first film layer is 0.1wt% to 1wt%; optionally, it is 0.3wt% to 0.6wt%; and / or, based on the total weight of the second film layer, the weight percentage of the conductive agent in the second film layer is 0.1wt% to 1wt%; optionally, it is 0.3wt% to 0.6wt%.
[0029] In the above technical solution, by reasonably setting the content of the conductive agent in the first film layer, it is beneficial to take into account the conductivity and bonding performance of the first film layer as well as the energy density and reliability of the battery cell; by reasonably setting the content of the conductive agent in the second film layer, it is beneficial to take into account the conductivity and bonding performance of the second film layer as well as the energy density of the battery cell.
[0030] In one possible implementation, the conductive agent includes at least one of superconducting carbon, conductive carbon black, Ketjen black, carbon dots, and carbon fibers. This facilitates flexible selection of the type of conductive agent based on actual conditions.
[0031] In one possible implementation, based on the total weight of the first film layer, the weight percentage of the binder in the first film layer is 1wt% to 2wt%; optionally, 1.2wt% to 1.4wt%; and / or, based on the total weight of the second film layer, the weight percentage of the binder in the second film layer is 1wt% to 2wt%; optionally, 1.2wt% to 1.4wt%.
[0032] In the above technical solution, by reasonably setting the content of the binder in the first film layer, it is beneficial to improve the bonding force between the first film layer and the second film layer or the positive electrode current collector, reduce the risk of wrinkling of the positive electrode sheet, and at the same time, it is beneficial to take into account the conductivity of the first film layer and the energy density and reliability of the battery cell; by reasonably setting the content of the binder in the second film layer, it is beneficial to improve the bonding force between the second film layer and the first film layer or the positive electrode current collector, reduce the risk of wrinkling of the positive electrode sheet, and at the same time, it is beneficial to take into account the conductivity of the second film layer and the energy density of the battery cell.
[0033] In one possible implementation, the binder includes: polyvinylidene fluoride, styrene polybutadiene rubber, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer and at least one of fluorine-containing acrylic resin, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, and polyarylate.
[0034] In a second aspect, a method for preparing a positive electrode pole piece is provided, comprising: providing a positive electrode current collector; preparing a first film layer and a second film layer on the same side of at least one surface of the positive electrode current collector; wherein the first film layer includes a first active material, the first active material including at least one of an olivine-structured material and a spinel-structured material; and the second film layer includes a second active material, the second active material including a layered material; and the resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy the following: 20 ≤ R2 / R1 ≤ 500. The positive electrode pole piece prepared by this method, when used in a battery cell, can improve the performance of the battery cell.
[0035] In a third aspect, a battery cell is provided, comprising the positive electrode sheet according to the first aspect and any possible implementation thereof.
[0036] In a fourth aspect, a battery is provided, comprising the battery cell described in the third aspect.
[0037] In a fifth aspect, an electrical device is provided, comprising the battery described in the fourth aspect.
[0038] The present invention provides a positive electrode sheet comprising a positive electrode current collector and a first film layer and a second film layer disposed on the same side of at least one surface of the positive electrode current collector. The first film layer comprises a first active material comprising at least one of an olivine-structured material and a spinel-structured material; the second film layer comprises a second active material comprising a layered material. Battery cells fabricated with the first active material have high reliability, while battery cells fabricated with the second active material have high energy density. The provision of the first and second film layers not only helps balance energy density and reliability, but also reduces the likelihood of the first active material adhering to the surface of the second active material, thereby reducing electrons accumulated on the surface of the second active material and reducing the risk of excessive lithium ion release from the second active material, thereby improving the cycling performance of the battery cell. The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy the following relationship: 20 ≤ R2 / R1 ≤ 500. This minimizes the resistivity difference between the first and second active materials, reducing the effect of electron accumulation on the surface of the second active material on lithium ion release from the second active material, thereby improving the cycling performance of the battery cell. Therefore, the technical solution of the embodiment of the present application is conducive to improving the performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] FIG1 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;
[0040] FIG2 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;
[0041] FIG3 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application;
[0042] FIG4 is a schematic diagram of a method for preparing a positive electrode sheet according to an embodiment of the present application;
[0043] FIG5 is a schematic diagram of a battery cell according to an embodiment of the present application;
[0044] FIG6 is a schematic diagram of a battery module according to an embodiment of the present application;
[0045] FIG7 is a schematic diagram of a battery according to an embodiment of the present application;
[0046] FIG8 is a schematic diagram of an electrical device according to an embodiment of the present application. DETAILED DESCRIPTION
[0047] Below, with appropriate reference to the accompanying drawings, embodiments of the positive electrode sheet and its preparation method, battery cell, battery and electrical device of the present application are described in detail. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0048] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0050] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0051] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0052] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0053] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0054] This application uses lithium-ion batteries as an example. Lithium-ion batteries are a typical type of power battery. Because they rely on the chemical reaction of lithium ions intercalating and deintercalating between the positive and negative electrodes to charge and discharge, lithium-ion batteries are also called rocking-chair batteries. During the charging process of a lithium-ion battery, lithium ions are released from the positive electrode, transferred through the electrolyte, and embedded in the active material of the negative electrode. During the discharge process, lithium ions are released from the negative electrode, transferred through the electrolyte, and embedded in the active material of the positive electrode.
[0055] It should be understood that the "lithium insertion" and "intercalation" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "de-lithiumization", "de-lithiumization" and "de-intercalation" processes described in this application refer to the process in which lithium ions are removed from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.
[0056] Lithium-ion batteries are widely used in mobile phones, electric vehicles, power stations, and other fields due to their high energy density, high voltage, and long cycle performance. As a component of a battery cell, the performance of the positive electrode is crucial to the performance of the battery cell.
[0057] The positive electrode sheet includes a positive electrode current collector and a film layer coated on the surface of the positive electrode current collector. The active material in the film layer is typically lithium iron phosphate with an olivine structure or a ternary material with a layered structure. When the film layer in the positive electrode sheet only includes lithium iron phosphate active material, although the battery cell prepared from the positive electrode sheet has high reliability, the energy density of the battery cell is low. When the film layer in the positive electrode sheet only includes ternary active material, although the battery cell prepared from the positive electrode sheet has high energy density, the reliability of the battery cell is low.
[0058] Mixing lithium iron phosphate and lithium nickel cobalt aluminum oxide as active materials to prepare a film layer on the surface of the positive electrode current collector is beneficial to taking into account both the energy density and reliability of the battery cell. However, after the lithium iron phosphate and lithium nickel cobalt aluminum oxide are mixed, the lithium iron phosphate is coated on the surface of the lithium nickel cobalt aluminum oxide. Due to the large difference in electrical conductivity between lithium iron phosphate and lithium nickel cobalt aluminum oxide, during the charge and discharge process of the battery cell, a large number of electrons gather on the surface of the lithium nickel cobalt aluminum oxide, affecting the intercalation and deintercalation of lithium ions, thereby affecting the cycle performance of the battery cell.
[0059] In view of this, the present application provides a positive electrode plate, which includes a positive electrode current collector and a first film layer and a second film layer arranged on the same side of at least one side surface of the positive electrode current collector. The first active material in the first film layer has an olivine structure and / or a spinel structure, and the second active material in the second film layer has a layered structure. The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy 20≤R2 / R1≤500. In this way, the first active material and the second active material are located in different film layers, which reduces the possibility of the first active material adhering to the surface of the second active material and reduces the resistivity difference between the first active material and the second active material, thereby improving the effect of the aggregation of electrons on the surface of the second active material on the release of lithium ions from the second active material, and improving the cycle performance of the battery cell.
[0060] [Positive electrode]
[0061] Figure 1 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application. As shown in Figure 1 , the positive electrode sheet 1 includes a positive electrode current collector 10 , a first film layer 11 and a second film layer 12 disposed on the same side of at least one surface of the positive electrode current collector 10 .
[0062] The positive electrode current collector 10 has two surfaces arranged along its thickness direction, and the first film layer 11 and the second film layer 12 are arranged on the surface of the same side of the positive electrode current collector 10. Optionally, as shown in FIG1 , the first film layer 11 and the second film layer 12 are arranged on both surfaces of the positive electrode current collector 10.
[0063] Figure 2 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application. In some other embodiments, as shown in Figure 2 , a first film layer 11 and a second film layer 12 are provided on one of two opposite surfaces of the positive electrode current collector 10 along the thickness direction.
[0064] Optionally, along the thickness direction of the positive electrode current collector 10 (e.g., the z direction in FIG1 ), the first film layer 11 may be located between the positive electrode current collector 10 and the second film layer 12. In some other embodiments, the second film layer 12 is located between the positive electrode current collector 10 and the first film layer 11. The positional relationship between the first film layer 11 and the second film layer 12 can be set according to actual conditions and is not specifically limited in this embodiment of the present application.
[0065] The first film layer 11 includes a first active material, and the first active material includes at least one of an olivine structure material and a spinel structure material.
[0066] Olivine is a material's crystalline structure, which describes the spatial arrangement of atoms within the material. Materials with this structure are highly stable. When used in battery cells, they can reduce the risk of fire and explosion under high-temperature conditions, thereby improving battery reliability.
[0067] The olivine structured material may include various materials, such as LiFePO4.
[0068] A spinel structure is a type of crystal structure used in materials. When used in battery cells, materials with a spinel structure enhance battery reliability and help reduce the risk of fire and explosion.
[0069] The spinel structure material may include various materials, such as LiMn2O4.
[0070] The second film layer 12 includes a second active material, and the second active material includes a material with a layered structure.
[0071] A layered structure is a type of crystalline structure in a material. Materials with a layered structure have a higher specific capacity, which, when used in battery cells, can increase the energy density of the battery cells. Specifically, specific capacity refers to the ratio of the amount of electricity that an active material can release to its mass.
[0072] The material of the layered structure may include a variety of materials, such as LiMO2, where M includes at least one of Co, Ni, and Mn.
[0073] The first film layer 11 includes a first active material, and the second film layer 12 includes a second active material. The first film layer 11 and the second film layer 12 are different film layers. This reduces the possibility of contact between the first active material and the second active material, and reduces the risk of the first active material adhering to or coating the surface of the second active material. This further improves the phenomenon of electron aggregation on the surface of the second active material caused by the difference in electrical conductivity between the first and second active materials, thereby reducing the impact of the aggregated electrons on the release of lithium ions from the second active material, and thus improving the cycling performance of the battery cell.
[0074] The first film layer 11 includes a first active material, and the second film layer 12 includes a second active material. Compared to a battery cell comprising only the second active material (e.g., a layered ternary material), the positive electrode sheets of the present embodiment have a higher reliability and a lower probability of explosion in extreme situations (e.g., under needle penetration test conditions).
[0075] The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 20≤R2 / R1≤500.
[0076] The resistivity of the first active material may refer to the resistivity of the first active material in powder form; and the resistivity of the second active material may refer to the resistivity of the second active material in powder form.
[0077] By setting 20≤R2 / R1≤500, the difference in conductivity between the first active material and the second active material can be reduced, which is beneficial to improving the phenomenon of electron aggregation on the surface of the second active material caused by the excessive difference in conductivity between the first active material and the second active material. In turn, the effect of electron aggregation on the surface of the second active material on the release of lithium ions from the second active material can be reduced, thereby reducing the risk of excessive release of lithium ions from the second active material, which is beneficial to improving the cycle performance of the battery cell.
[0078] The cycling performance of a battery cell can be measured by its capacity retention, which is the ratio of retained capacity to initial discharge capacity. Retained capacity refers to the discharge capacity of a battery cell after completing a certain number of charge and discharge cycles. Initial discharge capacity refers to the discharge capacity of a battery cell during its first charge and discharge test.
[0079] Optionally, the positive electrode current collector 10 is aluminum foil, or a composite current collector formed of metal and polymer materials.
[0080] The positive electrode sheets of the embodiments of the present application can be used to prepare battery cells, which can be used in various electrical devices, such as electric vehicles, lighting tools, etc.
[0081] The embodiment of the present application provides a positive electrode plate 1, comprising a positive electrode current collector 10, and a first film layer 11 and a second film layer 12 arranged on the same side of at least one side surface of the positive electrode current collector 10. The first film layer 11 comprises a first active material, the first active material comprising at least one of an olivine structure material and a spinel structure material; the second film layer 12 comprises a second active material, the second active material comprising a layered structure material. The provision of the first film layer 11 and the second film layer 12, on the one hand, is conducive to taking into account both the energy density and reliability of the battery cell; on the other hand, it can reduce the possibility of the first active material adhering to or coating the surface of the second active material, thereby reducing the electrons gathered on the surface of the second active material, reducing the influence of the gathered electrons on the release of lithium ions from the second active material, and is conducive to improving the cycle performance of the battery cell. The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy the following relationship: 20 ≤ R2 / R1 ≤ 500. This minimizes the difference in resistivity between the first and second active materials, reducing the number of electrons that accumulate on the surface of the second active material. This, in turn, reduces the concentration of electrons on the surface of the second active material, reducing the impact of excessive lithium ion release from the second active material, and thus improving the cycling performance of the battery cell. Therefore, the technical solutions of the embodiments of the present application are beneficial for improving the performance of the battery cell.
[0082] In some embodiments, the resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 50≤R2 / R1≤300.
[0083] In this embodiment, by setting 50≤R2 / R1≤300, the difference in conductivity between the first active material and the second active material can be further reduced, the electrons accumulated on the surface of the second active material can be further reduced, and the risk of excessive release of lithium ions from the second active material can be reduced, which is beneficial to improving the cycle performance of the battery cell.
[0084] In some embodiments, the resistivity R1 of the first active material is 10 Ω·cm to 80 Ω·cm.
[0085] Optionally, the resistivity of the first active material is the resistivity measured at 4 MPa. Under different pressures, the resistivity of the first active material is different.
[0086] When the resistivity R1 of the first active material is less than 10Ω·cm, the preparation of the first active material is relatively complex. For example, a large amount of conductive material needs to be coated on the outer layer of the olivine structure material, which results in high cost and little improvement in energy density. In addition, it is not conducive to reducing the resistivity gap between the first active material and the second active material, and the cycle performance of the battery cell is only slightly improved.
[0087] When the resistivity R1 of the first active material is greater than 80Ω·cm, the conductivity of the first active material is low, which is not conducive to improving the conductivity of the first film layer 11 , affecting the overall capacity of the battery cell, and resulting in a small increase in energy density.
[0088] In this embodiment, the resistivity R1 of the first active material is 10Ω·cm to 80Ω·cm, which facilitates the preparation of the first active material and helps to take into account the conductivity of the first film layer 11 and the cycle performance of the battery cell, thereby improving the performance of the battery cell.
[0089] Optionally, the resistivity R1 of the first active material is 20 Ω·cm to 60 Ω·cm. This is beneficial to further improve the performance of the battery cell.
[0090] In some embodiments, the resistivity R2 of the second active material is 1500 Ω·cm to 15000 Ω·cm.
[0091] Optionally, the resistivity of the second active material is the resistivity measured at 4 MPa. Under different pressures, the resistivity of the second active material is different.
[0092] When the resistivity R2 of the second active material is less than 1500 Ω·cm, the preparation of the second active material is relatively complex and requires adjusting the synthesis process to synthesize extremely small grains, resulting in a high preparation cost.
[0093] When the resistivity R2 of the second active material is greater than 15,000 Ω·cm, the second active material has low conductivity, which is not conducive to improving the conductivity of the second film layer 12. In addition, it is not conducive to reducing the resistivity gap between the first active material and the second active material, and the cycle performance of the battery cell is not greatly improved.
[0094] Alternatively, the second active material with different resistivity can be obtained by changing the preparation process of the second active material, the ratio of the elements in the second active material, providing a conductive coating layer in the second active material, etc.
[0095] In this embodiment, the resistivity R2 of the second active material is 1500Ω·cm to 15000Ω·cm, which facilitates the preparation of the second active material and helps to take into account the conductivity of the second film layer 12 and the cycle performance of the battery cell, thereby improving the performance of the battery cell.
[0096] Optionally, the resistivity R2 of the second active material is 3000 Ω·cm to 9000 Ω·cm. This is beneficial to further improve the performance of the battery cell.
[0097] In some embodiments, as shown in FIG. 1 and FIG. 2 , the second film layer 12 is located on a surface of the first film layer 11 away from the positive electrode current collector 10 .
[0098] The second film layer 12 is located on the surface of the first film layer 11 away from the positive electrode current collector 10 . That is, along the thickness direction of the positive electrode current collector 10 , the first film layer 11 is located between the positive electrode current collector 10 and the second film layer 12 .
[0099] Optionally, the first film layer 11 is in direct contact with the positive electrode current collector 10. For example, a slurry for preparing the first film layer 11 is coated on the surface of the positive electrode current collector 10, and after drying and other processes, the first film layer 11 is formed.
[0100] Optionally, the first film layer 11 is in direct contact with the second film layer 12. For example, after the first film layer is prepared, a slurry for preparing the second film layer 12 is applied to the surface of the first film layer 11, and after drying and other processes, the second film layer 12 is formed. For another example, a specific coating tool is used to simultaneously apply the corresponding slurry to the surface of the positive electrode current collector 10 to prepare the first film layer 11 and the second film layer 12.
[0101] In this embodiment, the second active material in the second film layer 12 includes a material having a layered structure, and the second film layer 12 is located on the surface of the first film layer 11 away from the positive electrode current collector 10. This is beneficial to reducing the transmission path of lithium ions to the second active material, which is beneficial to exerting the performance of the second active material, and thus is beneficial to improving the energy density and cycle performance of the battery cell.
[0102] FIG3 is a schematic diagram of a positive electrode sheet according to an embodiment of the present application. In some embodiments, as shown in FIG3 , the first film layer 11 is located on a surface of the second film layer 12 away from the positive electrode current collector 10 .
[0103] The first film layer 11 is located on the surface of the second film layer 12 away from the positive electrode current collector 10 . That is, along the thickness direction of the positive electrode current collector 10 , the second film layer 12 is located between the first film layer 11 and the positive electrode current collector 10 .
[0104] In this embodiment, the first film layer 11 is located on the surface of the second film layer 12 away from the positive electrode current collector 10. The first film layer 11 is located on the outermost side of the positive electrode current collector 10. This is beneficial to improving the reliability of the battery cell and reducing the risk of fire and explosion.
[0105] In some embodiments, the first active material includes a first active material core and a first coating layer coating the first active material core, the first active material core includes at least one of an olivine structure material and a spinel structure material, and the first coating layer includes a carbon material.
[0106] For example, materials with an olivine structure have poor conductivity. Providing a first coating layer on the surface of the first active material core can help improve the conductivity of the first active material. For example, the resistivity of the first active material can be varied by adjusting the mass fraction of the first coating layer in the first active material.
[0107] In this embodiment, the first coating layer coats the first active material core, which is beneficial to improving the conductivity of the first active material.
[0108] In some embodiments, the olivine structured material includes LiFe 1-x-y Mn x M 1 y PO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M 1 The present invention includes at least one of transition metal elements or non-transition metal elements other than Fe and Mn.
[0109] Optionally, M 1 Includes at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr.
[0110] Alternatively, LiFe 1-x-y Mn x M 1 y PO4 includes LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 In this way, the stability of the material with olivine structure is higher, which is beneficial to improve the reliability of the battery cell.
[0111] In some embodiments, the spinel structure material includes LiMn2O4, LiNi e Mn 2-e At least one of O4, wherein 0<e<2. The battery cell prepared by the spinel structure material has high reliability, which is beneficial to reducing the probability of fire and explosion of the battery cell.
[0112] In some embodiments, the layered structure material includes LiCoO2, LiMnO2, LiNiO2, LiNi a Co b Mn 1-a-b O2、LiNi c Co d Al 1-c-d O2、nLi2MnO3·(1-n)LiM 2 At least one of O2, wherein 0<n<1, M 2 The material comprises at least one of Co, Ni, and Mn, and 0<a<1, 0<b<1, 0<a+b<1, 0<c<1, 0<d<1, and 0<c+d<1. The layered structure material has a high specific capacity, which is beneficial to improving the energy density of the battery cell.
[0113] In the embodiment of the present application, during the charge and discharge process of the battery cell, the content of lithium ions will also change due to the deintercalation and consumption of lithium ions. Similarly, the content of oxygen ions will also change due to various circumstances. Therefore, the general formula of the olivine structure material, spinel structure material, and layered structure material measured by the positive electrode of the battery cell may be different from the general formula given above. For example, for LiCoO2, the general formula that may be measured is Li 1+u CoO 2+r , u is a number less than 0, and r is a number less than 0.
[0114] In some embodiments, the thickness d1 of the first film layer 11 is 40 μm to 160 μm.
[0115] When the thickness d1 of the first film layer 11 is not less than 40 μm, the first active material has a higher stability, and a thicker first film layer 11 is beneficial to improving the reliability of the battery cell; when the thickness d1 of the first film layer 11 is not greater than 160 μm, the first film layer 11 occupies a suitable space, and when the volume of the battery cell is limited, more space is provided for the second film layer 12, which is beneficial to improving the energy density of the battery cell.
[0116] In this embodiment, the thickness d1 of the first film layer 11 is 40 μm to 160 μm, which is beneficial for taking both the reliability and energy density of the battery cell into consideration.
[0117] The thickness of the first film layer 11 and the second film layer 12 can be measured by a scanning electron microscope, for example, by the magnification of the scanning electron microscope and the size of the image obtained by the scanning electron microscope.
[0118] Optionally, the thickness d1 of the first film layer 11 is 60 μm to 140 μm, which is conducive to further considering the process feasibility, performance reliability and energy density of the battery cell.
[0119] In this embodiment, by reasonably setting the thickness of the first film layer 11 , it is beneficial to take into account both the energy density and the reliability of the battery cell.
[0120] In some embodiments, the thickness d2 of the second film layer 12 is 40 μm to 160 μm.
[0121] When the thickness d2 of the second film layer 12 is not less than 40 μm, due to the high gram capacity of the second active material, a thicker second film layer 12 is beneficial to improving the energy density of the battery cell; when the thickness d2 of the second film layer 12 does not exceed 160 μm, under the condition that the volume of the battery cell is constant, more space can be provided for the first film layer, which is beneficial to improving the reliability of the battery cell.
[0122] In this embodiment, the thickness d2 of the second film layer 12 is 40 μm to 160 μm, which is beneficial for taking both the reliability and energy density of the battery cell into consideration.
[0123] Optionally, the thickness d2 of the second film layer 12 is 60 μm to 140 μm, which is beneficial for further taking into account the reliability and energy density of the battery cell.
[0124] In some embodiments, based on the total weight of the first film layer 11, the weight percentage of the first active material is 90wt% to 99wt%; optionally, 96wt% to 98wt%, for example, 97wt%; and / or, based on the total weight of the second film layer 12, the weight percentage of the second active material is 90wt% to 99wt%; optionally, 96wt% to 98wt%, for example, 97wt%.
[0125] When the mass ratio of the first active material to the first film layer 11 is not less than 90wt%, it is beneficial to improve the energy density of the battery cell; when the mass ratio of the first active material to the first film layer 11 exceeds 99wt%, a conductive agent, a binder, etc. can be added to the first film layer, which is beneficial to improve the conductivity of the first film layer 11 and the bonding force between the first film layer 11 and the positive electrode current collector 10 or the second film layer 12.
[0126] In this embodiment, by reasonably setting the mass ratio of the first active material to the first film layer 11 , it is beneficial to improve the comprehensive performance of the first film layer 11 , and to balance the energy density and reliability of the battery cell and the conductivity and adhesion of the first film layer 11 .
[0127] Similarly, by reasonably setting the mass ratio of the second active material to the second film layer 12 , the overall performance of the second film layer 12 is improved, and the energy density and reliability of the battery cell and the conductivity and adhesion of the second film layer 12 are balanced.
[0128] In some embodiments, based on the total weight of the first film layer 11, the weight percentage of the conductive agent in the first film layer 11 is 0.1wt% to 1wt%; optionally, it is 0.3wt% to 0.6wt%, for example, 0.5wt%; and / or, based on the total weight of the second film layer 12, the weight percentage of the conductive agent in the second film layer 12 is 0.1wt% to 1wt%; optionally, it is 0.3wt% to 0.6wt%, for example, 0.5wt%.
[0129] When the mass ratio of the conductive agent in the first film layer 11 to the first film layer 11 is not less than 0.1wt%, it is beneficial to improve the conductivity of the first film layer 11; when the mass ratio of the conductive agent in the first film layer 11 to the first film layer 11 is not higher than 1wt%, more first active material or binder can be added to the first film layer 11, which is beneficial to improve the bonding performance of the first film layer 11 or the energy density and reliability of the battery cell.
[0130] When the mass ratio of the conductive agent in the second film layer 12 to the second film layer 12 is not less than 0.1wt%, it is beneficial to improve the conductivity of the second film layer 12; when the mass ratio of the conductive agent in the second film layer 12 to the second film layer 12 is not higher than 1wt%, more second active material or binder can be added to the second film layer 12, which is beneficial to improve the bonding performance of the second film layer 12 or the energy density of the battery cell.
[0131] In this embodiment, by reasonably setting the content of the conductive agent in the first film layer 11, it is beneficial to take into account the conductivity and bonding performance of the first film layer 11 as well as the energy density and reliability of the battery cell; by reasonably setting the content of the conductive agent in the second film layer 12, it is beneficial to take into account the conductivity and bonding performance of the second film layer 12 as well as the energy density of the battery cell.
[0132] In some embodiments, the conductive agent includes at least one of superconducting carbon, conductive carbon black, Ketjen black, carbon dots, and carbon fibers. This allows for flexible selection of the type of conductive agent based on actual conditions.
[0133] In some embodiments, based on the total weight of the first film layer 11, the weight percentage of the binder in the first film layer 11 is 1wt% to 2wt%; optionally, it is 1.2wt% to 1.4wt%, for example, 1.3wt%; and / or, based on the total weight of the second film layer 12, the weight percentage of the binder in the second film layer 12 is 1wt% to 2wt%; optionally, it is 1.2wt% to 1.4wt%, for example, 1.3wt%.
[0134] When the mass ratio of the binder in the first film layer 11 to the first film layer 11 is not less than 1wt%, it is beneficial to improve the bonding performance of the first film layer 11; when the mass ratio of the binder in the first film layer 11 to the first film layer 11 is not higher than 2wt%, more first active material or conductive agent can be added to the first film layer 11, which is beneficial to improve the conductivity of the first film layer 11 or the energy density and reliability of the battery cell.
[0135] When the mass ratio of the binder in the second film layer 12 to the second film layer 12 is not less than 1wt%, it is beneficial to improve the bonding performance of the second film layer 12; when the mass ratio of the binder in the second film layer 12 to the second film layer 12 is not higher than 2wt%, more second active materials or conductive agents can be added to the second film layer 12, which is beneficial to improve the conductivity of the second film layer 12 or the energy density of the battery cell.
[0136] In this embodiment, by properly adjusting the binder content in the first film layer 11, the bonding strength between the first film layer 11 and the second film layer 12 or the positive electrode current collector 10 is improved, reducing the risk of wrinkling the positive electrode sheet. This also helps balance the conductivity of the first film layer 11 with the energy density and reliability of the battery cell. By properly adjusting the binder content in the second film layer 12, the bonding strength between the second film layer 12 and the first film layer 11 or the positive electrode current collector 10 is improved, reducing the risk of wrinkling the positive electrode sheet. This also helps balance the conductivity of the second film layer 12 with the energy density of the battery cell.
[0137] In the embodiment of the present application, the types and contents of the binder and the conductive agent in the first film layer 11 and the second film layer 12 can be flexibly set according to actual conditions, as long as they meet the above reasonable ranges.
[0138] In some embodiments, the binder includes: polyvinylidene fluoride, styrene polybutadiene rubber, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer and at least one of fluorine-containing acrylic resin, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, and polyarylate.
[0139] [Preparation method of positive electrode sheet]
[0140] FIG4 is a schematic diagram of a method for preparing a positive electrode sheet according to an embodiment of the present application. The present application provides a method for preparing a positive electrode sheet, as shown in FIG4 , wherein the method 200 includes the following steps.
[0141] Step 210 : providing a positive electrode current collector 10 .
[0142] Step 220: Prepare a first film layer 11 and a second film layer 12 on the same side of at least one surface of the positive electrode current collector 10. The first film layer 11 includes a first active material, which includes at least one of an olivine-structured material and a spinel-structured material; the second film layer 12 includes a second active material, which includes a layered material; and the resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy the following: 20 ≤ R2 / R1 ≤ 500.
[0143] The positive electrode sheet prepared by this method is beneficial to improving the performance of the battery cell when applied to the battery cell.
[0144] [Battery Cell]
[0145] The present application provides a battery cell, comprising the positive electrode sheet in the above embodiment.
[0146] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square, or any other shape.
[0147] FIG5 is a schematic diagram of a battery cell according to an embodiment of the present application. As shown in FIG5 , the battery cell 4 includes a housing 31 , a cover plate 32 , and an electrode assembly 33 disposed in the housing 31 .
[0148] The electrode assembly 33 can be made of the positive electrode sheet, the negative electrode sheet and the separator of the present application through a winding process or a lamination process.
[0149] Optionally, the battery cell 3 further includes an electrolyte. The electrolyte can be solid, semi-solid, or liquid, and this embodiment of the application does not impose any specific limitation on this.
[0150] In some embodiments, battery cells may be assembled into a battery module. The number of battery cells contained in a battery module may be one or more. The specific number may be selected by those skilled in the art based on the application and capacity of the battery module.
[0151] Figure 6 is a schematic diagram of a battery module according to one embodiment of the present application. Referring to Figure 6 , within a battery module 4, multiple battery cells 3 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 3 may be secured together using fasteners.
[0152] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 3 are accommodated in the accommodation space.
[0153] [Battery]
[0154] The present application provides a battery, comprising the battery cell described in the above embodiment.
[0155] Figure 7 is a schematic diagram of a battery according to an embodiment of the present application. As shown in Figure 7 , the present application provides a battery 5 comprising the battery cell 3 according to any of the above embodiments.
[0156] The battery cells 3 can be directly assembled into the battery 5 , or they can be assembled into battery modules first, and then multiple battery modules can be assembled into the battery 5 .
[0157] [Electrical devices]
[0158] The present application provides an electrical device, comprising the battery described in the above embodiment.
[0159] Figure 8 is a schematic diagram of an electric device according to an embodiment of the present application. As shown in Figure 8 , the present application provides an electric device 6 including the battery 5 according to the above embodiment.
[0160] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0161] [Example]
[0162] Example 1
[0163] The structure of the positive electrode sheet in Example 1 can be seen in Figure 1. In Example 1, the positive electrode current collector 10 is an aluminum foil with a thickness of 13 μm, the thickness d1 of the first film layer 11 is 120 μm, and the thickness d2 of the second film layer 12 is 80 μm.
[0164] In the first film layer 11, the first active material is LiFePO4 (also referred to as LFP) with a carbon coating layer, and the resistivity of the first active material is 30 Ω·cm at 4 MPa. The first film layer 11 also includes conductive carbon black as a conductive agent and polyvinylidene fluoride (PVDF) as a binder. Based on the total weight of the first film layer 11, the weight content of the first active material in the first film layer 11 is 97 wt%, the weight content of the conductive agent in the first film layer 11 is 1 wt%, and the weight content of the binder in the first film layer 11 is 2 wt%.
[0165] In the second film layer 12, the second active material is LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM), the second active material has a resistivity of 4500 Ω·cm at 4 MPa. The second film layer 12 also includes conductive carbon black as a conductive agent and PVD as a binder. Based on the total weight of the second film layer 12, the weight content of the second active material in the second film layer 12 is 97 wt%, the weight content of the conductive agent in the second film layer 12 is 1 wt%, and the weight content of the binder in the second film layer 12 is 2 wt%.
[0166] The ratio of the resistivity R2 of the second active material to the resistivity R1 of the first active material is 150.
[0167] Examples 2-7
[0168] The difference between Example 2-7 and Example 1 is that R2 / R1 is different.
[0169] In the embodiment, R2 / R1 are respectively: 20, 50, 120, 180, 300, 500.
[0170] Examples 8-12
[0171] The difference between Examples 8-10 and Example 1 is that the values of R1 and R2 are different.
[0172] In Example 8, R1 is 10, R2 is 1500, and R2 / R1 is 150.
[0173] In Example 9, R1 is 20, R2 is 3000, and R2 / R1 is 150.
[0174] In Example 10, R1 is 50, R2 is 7500, and R2 / R1 is 150.
[0175] In Example 11, R1 is 60, R2 is 9000, and R2 / R1 is 150.
[0176] In Example 12, R1 is 80, R2 is 12000, and R2 / R1 is 150.
[0177] Examples 13-16
[0178] The difference between Examples 13-16 and Example 1 is that the thickness d1 of the first film layer 11 is different.
[0179] In Examples 13-16, the thickness d1 of the first film layer 11 is 40 μm, 60 μm, 140 μm, and 160 μm, respectively.
[0180] Examples 17-20
[0181] The difference between Examples 17-20 and Example 1 is that the thickness d2 of the second film layer 12 is different.
[0182] In Examples 17-20, the thickness d2 of the first film layer 12 is 40 μm, 60 μm, 140 μm, and 160 μm, respectively.
[0183] Examples 21-23
[0184] The difference between Example 21 and Example 1 is that the first active material is lithium manganese iron phosphate LiFe 0.5 Mn 0.5 PO4, abbreviated as LFMP.
[0185] The difference between Example 22 and Example 1 is that the first active material is LiMn2O4.
[0186] The difference between Example 23 and Example 1 is that the first active material is LiMn2O4 and LiFePO4, and the mass ratio of the two is 1:1.
[0187] Example 24
[0188] The difference between Example 24 and Example 1 is that the second active material is a lithium-rich manganese-based material Li 1.2 Ni 0.54 Co 0.13 Mn0. 13 O2, abbreviated as LRNCM.
[0189] Examples 25-26
[0190] The difference between Examples 25-26 and Example 1 is that the structure of the positive electrode plate 1 is different. The structure can be seen in Figures 2 and 3.
[0191] Comparative Example 1
[0192] The difference between Comparative Example 1 and Example 1 is that the structure in which the first film layer and the second film layer are layered is not adopted.
[0193] In Comparative Example 1, LiFePO4 and LiNi 0.6 Co 0.2 Mn 0.2 After O2 is mixed in a certain mass ratio, conductive agent carbon black, binder PVDF and N-methylpyrrolidone (NMP) are added to prepare the positive electrode active slurry, which is coated on aluminum foil and dried to form the positive electrode sheet.
[0194] Comparative Example 2
[0195] The difference between Comparative Example 2 and Comparative Example 1 is that R2 / R1 is 700.
[0196] In Table 1, R1 represents the resistivity of the powder of the first active material, R2 represents the resistivity of the powder of the second active material, d1 represents the thickness of the first film layer 11, d2 represents the thickness of the second film layer 12, Q1 represents the cycle capacity retention rate of the battery cell at 25°C, Q2 represents the cycle capacity retention rate of the battery cell at 45°C, and Q3 represents the energy density of the battery cell.
[0197] [Preparation of battery cells]
[0198] (1) Preparation of positive electrode sheet
[0199] To prepare the slurry for the first membrane layer, the first active material, conductive agent, binder, and NMP were mixed and stirred to form a slurry. To prepare the slurry for the second membrane layer, the second active material, conductive agent, binder, and NMP were mixed and stirred to form a slurry. The types and proportions of the various materials for the slurries of the first and second membrane layers are shown in Tables 1 and 2.
[0200] The slurry of the first film layer and the slurry of the second film layer were applied to the surface of the positive electrode current collector aluminum foil using an extrusion coating device. After drying and cold pressing, the positive electrode sheet was obtained. The thickness of the first film layer and the second film layer can be seen in Table 1.
[0201] (2) Preparation of negative electrode sheet
[0202] The negative electrode active material graphite, the conductive agent acetylene black, the binder styrene butadiene rubber, and the thickener sodium carboxymethyl cellulose are mixed in a weight ratio of graphite: acetylene black: styrene butadiene rubber: sodium carboxymethyl cellulose = 95:2:2:1, and an appropriate amount of deionized water is added and stirred thoroughly to form a uniform negative electrode slurry; the slurry is coated on the negative electrode current collector copper foil, dried, and cold pressed to obtain a negative electrode sheet.
[0203] (3) Preparation of electrolyte
[0204] In an argon atmosphere glove box with a water content of <10ppm, one or more solvents are mixed in a weight ratio to obtain a mixed solvent. A certain mass of fully dried lithium salt LiPF6 is dissolved in the above mixed solvent, and then an inorganic lithium salt additive is added thereto. After stirring evenly, an electrolyte is obtained.
[0205] (4) Preparation of battery cells
[0206] The positive electrode sheet, the separator (polyethylene porous polymer film), and the negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain the electrode assembly; the electrode assembly is placed in a shell, and the prepared electrolyte is injected into the shell, and then after vacuum packaging, standing, formation, shaping and other processes, a battery cell is obtained.
[0207] [Determination of the First Active Material and the Second Active Material]
[0208] Take a certain mass of active material layer, prepare the sample by grinding, pressing, etc., use X-ray diffraction instrument to scan at 5° / min, 10-80°, and compare with the characteristic peaks of the corresponding material to confirm the type of active material.
[0209] [Determination of resistivity of active material powder]
[0210] Weigh a sample of a certain mass, adjust the depth of the feeding chamber of the test instrument (a powder resistivity tester such as the ST2722 digital four-probe tester can be used), add the sample to the feeding chamber, apply pressure from 0 to 25 MPa, and record the powder resistivity test results at different pressure points. The resistivity in this application example is described using 4 MPa as an example.
[0211] [Cycling performance test]
[0212] At 25 / 45°C, the battery cell is first charged to 4.3V at a constant current of 1C, then further charged at a constant voltage of 4.3V to a current of 0.05C, and then discharged to 3V at a constant current of 1C. This constitutes one charge-discharge cycle, and the discharge capacity at this time is the discharge capacity of the first cycle. The battery is subjected to multiple charge-discharge cycles as described above, and the discharge capacity of the 200th cycle is detected. The capacity retention rate of the battery cell after 200 cycles is calculated using the following formula: Capacity retention rate of the battery after 200 cycles (wt%) = [discharge capacity of the 200th cycle / discharge capacity of the first cycle] × 100wt%.
[0213] [Acupuncture test]
[0214] Charge the battery cell to full charge and place it on the puncture sample table. Use a 3mm steel needle to pierce the battery plate at a speed of 1mm / s from a direction perpendicular to the battery plate. The piercing position should be close to the geometric center of the pierced surface until it is completely punctured or thermal runaway occurs.
[0215] In the embodiment of the present application, both the appearance of smoke and the valve opening and the fire without explosion indicate that the needle penetration test has been passed. In other words, the absence of explosion indicates that the needle penetration test has been passed.
[0216] [Energy density test]
[0217] At room temperature (25℃±2℃), discharge to the lower limit voltage in the form of constant current discharge (1 / 3C rate), let it stand for 30 minutes, and then charge to the upper limit cut-off voltage in a constant current and constant voltage charging mode (constant current 1 / 3C, constant voltage charging to 1 / 20C), let it stand for 30 minutes, and calculate the discharge energy E (in Wh). Repeat 3 times, take the average of the 3 discharge energies E, and divide it by the volume V of the hard-shell battery cell, then the volume energy density (in Wh / L) = Eaverage / V.
[0218] As shown in Examples 1-26 and Comparative Examples 1-2, the first active material and the second active material are arranged in different film layers, and the resistivities of the first active material and the second active material satisfy a certain relationship, which can improve the early capacity attenuation of the battery cell, and is beneficial to improving the cycle performance of the battery cell, thereby helping to improve the performance of the battery cell.
[0219] As shown in Examples 2-7, the reasonable setting of the resistivity relationship between the first active material and the second active material is conducive to further reducing the capacity attenuation in the early stage of the cycle and improving the cycle performance of the battery cell. As shown in Examples 8-12, the reasonable setting of the resistivity of the first active material and the second active material can facilitate the preparation of the first active material and the second active material while improving the cycle performance of the battery cell. As shown in Examples 13-20, the reasonable setting of the thickness of the first film layer and the second film layer can facilitate the flexible selection of the required energy density, reliability, etc. of the battery cell according to actual conditions while improving the cycle performance of the battery cell. As shown in Examples 21-24, the technical solutions of the embodiments of the present application can be applied to a variety of different active materials. As shown in Examples 25-26, the technical solutions of the embodiments of the present application can be applied to positive electrode sheets of various structures.
[0220] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: include: A positive electrode current collector (10) and a first film layer (11) and a second film layer (12) arranged on the same side of at least one surface of the positive electrode current collector (10); wherein: The first film layer (11) includes a first active material, and the first active material includes at least one of an olivine structure material and a spinel structure material; The second film layer (12) comprises a second active material, wherein the second active material comprises a material having a layered structure; The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 20≤R2 / R1≤500.
2. The positive electrode sheet according to claim 1, characterized in that: The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 50≤R2 / R1≤300.
3. The positive electrode sheet according to claim 1 or 2, characterized in that: The resistivity R1 of the first active material is 10 Ω·cm to 80 Ω·cm; alternatively, 20 Ω·cm to 60 Ω·cm.
4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: The resistivity R2 of the second active material is 1500 Ω·cm to 15000 Ω·cm; optionally, 3000 Ω·cm to 9000 Ω·cm.
5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The second film layer (12) is located on a surface of the first film layer (11) away from the positive electrode current collector (10).
6. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: The first film layer (11) is located on a surface of the second film layer (12) that is away from the positive electrode current collector (10).
7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The first active material includes a first active material core and a first coating layer coating the first active material core, the first active material core includes at least one of the olivine structure material and the spinel structure material, and the first coating layer includes a carbon material.
8. The positive electrode sheet according to any one of claims 1 to 7, characterized in that: The olivine structured material includes LiFe 1-x-y Mn x M 1 y PO4, 0≤x≤1, 0≤y<1, 0≤x+y≤1, M 1 Including at least one of other transition metal elements or non-transition metal elements except Fe and Mn; Optionally, M 1 Including at least one of Cr, Mg, Ti, Al, Zn, W, Nb, and Zr; Optionally, the LiFe 1-x-y Mn x M 1 y PO4 includes LiFePO4, LiMnPO4, LiFe 0.5 Mn 0.5 At least one of PO4.
9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The spinel structure material includes LiMn2O4, LiNi e Mn 2-e At least one of O4, wherein 0<e<2.
10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The layered structure material includes LiCoO2, LiMnO2, LiNiO2, LiNi a Co b Mn 1-a-b O2、LiNi c Co d Al 1-c-d O2、nLi2MnO3·(1-n)LiM 2 O2, wherein 0<a<1, 0<b<1, 0<a+b<1, 0<c<1, 0<d<1, 0<c+d<1, 0<n<1, M 2 Includes at least one of Co, Ni, and Mn.
11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: The thickness d1 of the first film layer (11) is 40 μm to 160 μm; optionally, 60 μm to 140 μm.
12. The positive electrode sheet according to any one of claims 1 to 11, characterized in that: The thickness d2 of the second film layer (12) is 40 μm to 160 μm; optionally, 60 μm to 140 μm.
13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: Based on the total weight of the first film layer (11), the weight percentage of the first active material is 90wt% to 99wt%; alternatively, 96wt% to 98wt%; and / or, Based on the total weight of the second film layer (12), the weight percentage of the second active material is 90wt% to 99wt%; alternatively, 96wt% to 98wt%.
14. The positive electrode sheet according to any one of claims 1 to 13, characterized in that: Based on the total weight of the first film layer (11), the weight percentage of the conductive agent in the first film layer (11) is 0.1wt% to 1wt%; optionally, 0.3wt% to 0.6wt%; and / or, Based on the total weight of the second film layer (12), the weight percentage of the conductive agent in the second film layer (12) is 0.1 wt% to 1 wt%; optionally, 0.3 wt% to 0.6 wt%.
15. The positive electrode sheet according to claim 14, characterized in that: The conductive agent includes at least one of superconducting carbon, conductive carbon black, Ketjen black, carbon dots and carbon fibers.
16. The positive electrode sheet according to any one of claims 1 to 15, characterized in that: Based on the total weight of the first film layer (11), the weight percentage of the binder in the first film layer (11) is 1wt% to 2wt%; optionally, 1.2wt% to 1.4wt%; and / or, Based on the total weight of the second film layer (12), the weight percentage of the binder in the second film layer (12) is The content is 1wt% to 2wt%; optionally, 1.2wt% to 1.4wt%.
17. The positive electrode sheet according to claim 16, characterized in that: The binder includes: at least one of polyvinylidene fluoride, styrene polybutadiene rubber, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-trichloroethylene copolymer and fluorine-containing acrylic resin, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate, polyethylene oxide, and polyarylate.
18. A method for preparing a positive electrode sheet, characterized in that: include: Providing a positive electrode current collector (10); A first film layer (11) and a second film layer (12) are prepared on the same side of at least one surface of the positive electrode current collector (10); wherein: The first film layer (11) includes a first active material, and the first active material includes at least one of an olivine structure material and a spinel structure material; The second film layer (12) comprises a second active material, wherein the second active material comprises a material having a layered structure; The resistivity R1 of the first active material and the resistivity R2 of the second active material satisfy: 20≤R2 / R1≤500.
19. A battery cell, characterized in that: Comprising the positive electrode sheet as described in any one of claims 1-17.
20. A battery, characterized in that: Comprising the battery cell as claimed in claim 19.
21. An electrical device, characterized in that: Comprising the battery of claim 20.
Citation Information
Cited By
Battery positive electrode, preparation method thereof and lithium ion battery
CN119864366A
Battery positive electrode and preparation method thereof, lithium ion battery
CN119864366B